Preferences for mHealth Physical Activity Interventions during Chemotherapy for Breast Cancer: A Qualitative Evaluation - Nielsen, Anne M. (Support Care Cancer, 2019)
PURPOSE: Physical activity has been shown to decline over the course of chemotherapy in breast cancer survivors; yet it may reduce treatment-related side effects and emerging evidence indicates it may improve disease outcomes. Mobile health (mHealth) interventions may be an effective, scalable strategy to increase physical activity during treatment. However, little is known about breast cancer patients’ interests and preferences for these interventions. It is important to understand patients’ interests and preferences prior to development of mHealth physical activity interventions to increase their relevance and efficacy. METHODS: Breast cancer survivors (n=30) participated in a semi-structured phone interview and asked about barriers and facilitators to physical activity during chemotherapy as well as their preferences on a range of potential mHealth intervention features. Transcribed interviews were coded and key themes were analyzed using an iterative, inductive approach. RESULTS: Five key themes were extracted from the interviews: 1) Need for education about physical activity during chemotherapy; 2) Treatment side effects inhibit physical activity; 3) A structured, home-based, tech-supported program with in-person elements is most feasible; 4) Need for a personalized, highly tailored intervention; and 5) Importance of social support from other breast cancer survivors, friends, and family. CONCLUSIONS: Breast cancer survivors are interested in mHealth physical activity interventions during chemotherapy but preferences for intervention content and delivery varied. Future work should engage patients and survivors in intervention development and testing.